Sociohistorical linguistics in Southeast Asia : new horizons for Tibeto-Burman Studies in honor of David Bradley - Sizhi Ding, Picus; Pelkey, Jamin (Brill's Tibetan studies library., 2017)
Sociohistorical Linguistics in Southeast Asia' blends insights from sociolinguistics, descriptive linguistics and historical-comparative linguistics to shed new light on regional Tibeto-Burman language varieties and their relationships across spatial, temporal and cultural differences. The approach is inspired by leading Tibeto-Burmanist, David Bradley, to whom the book is dedicated. The volume includes twelve original research essays written by eleven Tibeto-Burmanists drawing on first-hand field research in five countries to explore Tibeto-Burman languages descended from seven internal sub-branches. Following two introductory chapters, each contribution is focused on a specific Tibeto-Burman language or sub-branch, collectively contributing to the literature on language identification, language documentation, typological analysis, historical-comparative classification, linguistic theory, and language endangerment research with new analyses, state-of-the-art summaries and contemporary applications.